2

Given the augmentation axiom and the decomposition axioms of functional dependencies and a relation of R(A,B,C) with an FD of: A -> B

I can augment A -> B with C to get AC -> BC.

Can I then decompose AC -> BC to get AC -> B?

4

Community wiki answer:

Yes. You can decompose to get AC -> B and AC -> C.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.